2021
DOI: 10.1002/admi.202101473
|View full text |Cite
|
Sign up to set email alerts
|

Chipset Nanosensor Based on N‐Doped Carbon Nanobuds for Selective Screening of Epinephrine in Human Samples

Abstract: Chipset nanosensor design and fabrication are important for healthcare research and development. Herein, a functionalized chipset nanosensor is designed to monitor neurotransmitters (i.e., epinephrine (EP)) in human fluids. An interdigitated electrode array (IDA) is functionalized by N‐doped carbon nanobud (N‐CNB) and N‐doped carbon nanostructure (N‐CNS). The surface morphology of N‐CNB shows the formation of nanotubular‐like branches on sheets and micrometer‐size tubes. The N‐CNS design consists of the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The presence of N atoms in the graphitic carbon chain breaks the carbon electroneutrality and creates abundant active sites with a partially polarized surface of positive and negative charges. This functionality arises from the difference in the electronegativity and electron configuration between N and C atoms [39,40]. Thus, the preparation of N-doped carbon-based materials with a novel procedure, porous network, high surface area, long durability, highly stable structure, and homogenous atomic distribution produces highly active materials with synergetic catalytic activity and high charge mobility and electron density.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of N atoms in the graphitic carbon chain breaks the carbon electroneutrality and creates abundant active sites with a partially polarized surface of positive and negative charges. This functionality arises from the difference in the electronegativity and electron configuration between N and C atoms [39,40]. Thus, the preparation of N-doped carbon-based materials with a novel procedure, porous network, high surface area, long durability, highly stable structure, and homogenous atomic distribution produces highly active materials with synergetic catalytic activity and high charge mobility and electron density.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenaline (4-[(1 R)−1-hydroxy-2-(methylamino)ethyl]benzene-1,2-diol; AD) is a catecholamine neurotransmitter, 1,2 and the adrenal glands and certain neurons usually secrete AD in physiological stress or hypoglycemia. 1,3 AD plays an important role in the regulation of the sympathetic nervous system, and its imbalance concentration is responsible for heart disease, thyroid hormone diseases, schizophrenic disease, Parkinson's disease, Huntington's disease, and Alzheimer's disease.…”
mentioning
confidence: 99%
“…Among different analytical detection techniques, the electrochemical system exhibited the advantages of high signaling amplification, easy fabrication, simple operation, low cost, and rapid detection. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] It has been reported that due to sluggish electrode kinetics and high overpotential, the conventional electrodes provided negligible response toward electrochemical oxidation of AD. 3,6 Furthermore, in physiological samples AD usually coexist with other biomolecules such as dopamine (DA), ascorbic acid (AA), and Uric acid (UA).…”
mentioning
confidence: 99%